Paramagnetic and Diamagnetic Susceptibility of Infinite Quantum Well - Adam Badra Cahaya (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2020)
Paramagnetism and diamagnetism of a material characterized by its magnetic susceptibility. When a material is exposed to an external magnetic field, magnetic susceptibility is defined as the ratio of the induced magnetization and the magnetic field. A paramagnetic material has magnetic susceptibility with positive sign. On the other hand, a diamagnetic material has magnetic susceptibility with negative sign. Atomically, paramagnetic materials consist of atoms that has orbital with unpaired electrons. Theoretical study of paramagnetic susceptibility and diamagnetic susceptibility are well described by Pauli paramagnetism and Landau diamagnetism, respectively. Although paramagnetism and diamagnetism are among the simplest magnetic properties of material that are studied in basic physics, theoretical derivations of Pauli paramagnetic and Landau diamagnetic susceptibility require second quantization formalism of quantum mechanics. We aim to discuss the paramagnetic and diamagnetic susceptibilities for simple three-dimensional quantum well using first quantization formalism.